Refused-knowledge during the COVID-19 Pandemic: Mobilising Experiential Expertise for Care and Well-being. (2nd January 2023) - Crabu, Stefano; Picardi, Ilenia; Turrini, Valentina
ABSTRACT: Since the early period of the COVID-19 pandemic concerned groups of people have produced knowledge refused by institutional science of how to manage public health and individual well-being in everyday pandemic life. Research in science and technology studies seeks to understand the social and cultural conditions under which contestation over scientific knowledge claims occurs. In the Italian case, 'refused' knowledge claims emerging outside institutionalised science play a performative role in questioning the current models for managing individual and public health. Such refused claims ascribe novel meanings to the COVID-19 pandemic and orient the ways in which people manage their own health and well-being during their everyday life. Two interrelated dimensions are at stake in the production and enactment of refused knowledge: (1) how experiential expertise is mobilised to reframe one's body in a process of self-care, thus validating a corpus of refused knowledge through personal experience, and (2) how narratives demarcate between a body of refused knowledge and the prevalent biomedical paradigms as a way of gaining experiential epistemic autonomy.